Storage duration impacts on nutritional composition and quality of table eggs (Bangladesh Journal of Animal Science, 2023)
This study was carried out to evaluate the effect of the duration of storage of ISA brown eggs at room temperature on the nutritional composition and quality of eggs. A total of one hundred and twenty (120) freshly laid eggs by 36 weeks old ISA brown layers were randomly collected and stored at room temperature for 21 days. On each sampling day (at week 0, week 1, week 2, and week 3 of storage), 30 eggs were broken to determine internal and external egg quality traits, proximate composition, and mineral profile.  Collected data were subjected to statistical analysis. Duration of storage had a significant effect (p